Hedonic Assessment of Coffee Processed with Pineapple Extract - Wiwik Endah Rahayu; Desy Triastuti; Fenny Aprilliani; Putri Citra Pratiwi; Jawad Ahmed Hasan; Kori Rahma Mardika (Green Engineering Society, 2026)
This study investigated the effects of steaming duration and pineapple peel-flesh extract proportions on the sensory acceptance of Arabica coffee processed with Subang pineapple extract. A Completely Randomized Design (CRD) was used with two factors: steaming duration (30, 60, and 90 minutes) and pineapple peel:flesh extract ratios (25:75, 50:50, and 75:25). Hedonic preference tests were conducted on selected sensory attributes of both ground and brewed coffee. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The result showed that steaming duration and pineapple extract ratio did not significantly affect the hedonic attributes of ground coffee. However, these factors influenced the color, aroma, body, acidity, and overall preference of brewed coffee. The optimal steaming duration was found to be between 30 and 60 minutes, with a pineapple peel extract ratio of pineapple peel and flesh extract of 75:25, resulting in the most preferred coffee according to panelists.